(3GdOQ GdeUhf aj EYQGH GdcJGH Gdecfhfs - (3GdSejf GdMdHjs
(3ChdgG (B:s
(3Chd GdehLhO efg (B" (3ai cJGH Hjf (B" (3hdG jLhR Cf jchf GSJKfGA jYed ajg dG jYdegG s
(3BNQgG (B:s
(3jfJgi HBNQ ShQI GdJhHI Hbhdg (B: (3dCf LYd GdYXje UaI ddg JYGdi Chdi ef LYdg UaI ddYQT Je GdLRA GdKGdK s
(3Hg CKGQ JbWjYs
(3cJHJ HNW bdjd GdfbWs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdfMhs